Aptamer-functionalized pH-sensitive liposomes for a selective delivery of echinomycin into cancer cells. Issue 47 (1st September 2021) - Lafi, Zainab; Alshaer, Walhan; Hatmal, Ma'mon M.; Zihlif, Malek; Alqudah, Dana A.; Nsairat, Hamdi; Azzam, Hanan; Aburjai, Talal; Bustanji, Yasser; Awidi, Abdalla
Abstract : Echinomycin was loaded into PEGylated pH-sensitive liposomes and functionalized with anti-nucleolin aptamer for selective targeting and pH-responsive release of echinomycin into cancer cells. Abstract : Echinomycin (quinomycin A) is a peptide antibiotic from the quinoxaline family, which has a DNA bifunctional intercalating activity and an inhibitor of hypoxia-inducible factor (HIF1α). Echinomycin was discovered in 1957 as a potent antitumor agent; however, it was not successful in clinical use due to its low water solubility and short half-life. To revitalize this potent drug, it is important to increase its aqueous solubility and bioavailability. In this study, echinomycin was loaded into PEGylated pH-sensitive liposomes (PEG LippH ) and functionalized with anti-nucleolin aptamer (AptNCL ) for selective targeting and pH-responsive release of echinomycin into cancer cells. Echinomycin was complexed with γ-cyclodextrin (ECγCD) to enhance its water solubility and then encapsulated into pH-sensitive liposomes (PEG LippH -ECγCD). Then, liposomes were functionalized with AptNCL (AptNCL-PEG LippH -ECγCD) and the successful functionalization was confirmed by dynamic light scattering (DLS) measurements and gel electrophoresis. Cellular uptake for AptNCL-PEG LippH was evaluated by flow cytometry analysis using MDA-MB-231, MCF7, A549 cancer cell lines with respect to the normal fibroblast cells. The results showed a higher uptake and selectivity for AptNCL-PEG LippH compared to PEG LippH . The anti-proliferative effects of AptNCL-PEG LippH -ECγCD were more potent than PEG LippH -ECγCD by 3.5, 4, and 5 folds for A549, MDA-MB-231, and MCF7, respectively. Selectivity indices (SI) for AptNCL-PEG LippH -ECγCD for the tumor cell lines compared to the normal cell line after 72 h were MDA-MB-231 (43.3), MCF7 (16.9), and A549 (8.5). Furthermore, SI after 3 h for the three cancer cell lines were 4.7, 2.5, 2.8, respectively.